2010
DOI: 10.2298/mpns1010630d
|View full text |Cite
|
Sign up to set email alerts
|

Individual renal hemodymamic response to chronic angiotensin II receptor bloc­kade and the influence on the renin-angiotensin system gene polymorphisms

Abstract: Our study shows that individual renal vascular response to losartan treatment in diabetic patients with persistent albuminuria, could be influenced by genetic polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(27 reference statements)
0
2
0
1
Order By: Relevance
“…Pathophysiological mechanisms that lead to the development of microalbuminuria in diabetic patients are complex and they are a result of the action of a numerous of hemodynamic and metabolic factors. Nowadays, it is believed that hemodynamic factors, such as systemic hypertension, glomerular hypertension and glomerular hyperfiltration, as well as ultrastructural changes at the level of the glomeruli such as thickening of the glomerular basement membrane and loss of negatively charged proteoglycans, are important factors in the development of albuminuria in diabetic nephropathy [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Pathophysiological mechanisms that lead to the development of microalbuminuria in diabetic patients are complex and they are a result of the action of a numerous of hemodynamic and metabolic factors. Nowadays, it is believed that hemodynamic factors, such as systemic hypertension, glomerular hypertension and glomerular hyperfiltration, as well as ultrastructural changes at the level of the glomeruli such as thickening of the glomerular basement membrane and loss of negatively charged proteoglycans, are important factors in the development of albuminuria in diabetic nephropathy [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation is the incomplete inhibition of renin-angiotensin system, since ACE inhibition does not cut off other alternative ways of angiotensin II production. Dragović et al showed that the individual hemodynamic response in the patients with diabetic nephropathy in the condition of renin-angiotensin system blockade is genetically dependent, as well as focusing on individual therapeutic strategies for the purpose of more effective prevention and prognosis of diabetic nephropathy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Smatra se da ovaj enzim ima značajnu ulogu u patogenezi bolesti. ACE takođe vrši hidrolizu bradikinina i supstancije P, proteina koji imaju značajnu ulogu u inflamaciji, aktivaciji makrofaga, limfocitnoj proli fe ra ciji i fagocitozi [14,15]. Upravo iz tog razloga ACE polimorfizam je jedan od najčešće ispitivanih polimorfizama u sarkoidozi.…”
Section: Uvodunclassified